1995
DOI: 10.1111/j.1476-5381.1995.tb13270.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic modelling of the haemodynamic effects of the A2a adenosine receptor agonist CGS 21680C in conscious normotensive rats

Abstract: 1 The aim of the present investigation was to determine the relationship between the blood concentration and haemodynamic effects of the adenosine Au receptor agonist, CGS 21680C (the sodium salt of 2-p-(2-carboxyethyl)phenylethylamino-5'-N-ethylcarboxamidoadenosine) in conscious normotensive rats.2 Chronically cannulated rats were randomly assigned to three groups which received 300, 1000 or 3000 jLg kg-' (0.56, 1.9 or 5.6 pmol kg-') of CGS 21680C intravenously over 15 min. The mean arterial blood pressure (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…The effects of regadenoson on MAP and HR described in the present study are consistent with those reported previously using known selective A 2A agonists (Webb et al, 1990;Koos et al, 1993;Mathot et al, 1995;Nekooeian and Tabrizchi, 1996;Alberti et al, 1997;Schindler et al, 2005). Hence, the decrease in MAP and tachycardia are commonly observed pharmacological effects of A 2A agonists.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The effects of regadenoson on MAP and HR described in the present study are consistent with those reported previously using known selective A 2A agonists (Webb et al, 1990;Koos et al, 1993;Mathot et al, 1995;Nekooeian and Tabrizchi, 1996;Alberti et al, 1997;Schindler et al, 2005). Hence, the decrease in MAP and tachycardia are commonly observed pharmacological effects of A 2A agonists.…”
Section: Discussionsupporting
confidence: 81%
“…The sinus tachycardia has been attributed to the baroreceptor reflex caused by the decrease in arterial pressure (Webb et al, 1990(Webb et al, , 1991Nekooeian and Tabrizchi, 1996;Alberti et al, 1997). However, there is also evidence that adenosine-mediated tachycardia can occur independent of a decrease in MAP (Lappe et al, 1992;Mathot et al, 1995;Koos and Chau, 1998;Schindler et al, 2005). Thus, the purpose of this study was to establish the role of A 2A adenosine receptors and the mechanism underlying the sinus Regadenososn is highly selective for the A 2A receptor subtype, has a rapid onset and short duration of action, is readily reversible, and causes sinus tachycardia in humans (Gao et al, 2001;Trochu et al, 2003;Hendel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic administration of selective A 2A R agonists can increase HR, probably due to reflex activation secondary to reduced blood pressure (6,31,32,34,35). In addition, there is evidence that there are ARs in the brain stem regulating cardiovascular control centers (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine, by acting on both A 1 and A 2A receptors, is implicated in the regulation of motor activity. There is clear experimental evidence for a central mediation of the motor-depressant effects of A 1 and A 2A receptor agonists (Snyder et al, 1981;Katz and Goldberg, 1987;Nikodijevic et al, 1990;Barraco et al, 1993;Marston et al, 1998), independent of their pronounced cardiovascular effects (Appel et al, 1995;Mathot et al, 1995). In contrast, some contradictory results exist regarding the motor-activating effects of adenosine antagonists and there is no consensus about the relative involvement of A 1 and A 2A receptors in caffeine-induced motor activation.…”
Section: Introductionmentioning
confidence: 91%